How Information Helps on Increasing Students' Understanding of Adolescent Reproductive Health At School - Insan Suwanto (STKIP Singkawang, 2021)
This study aims to describe the level of students' understanding of adolescent reproductive health and to examine how the influence of information on their level of understanding. The research used was pre-experimental designs with a one-group pretest-posttest design with a total sample of 41 people. The instruments used in this study were the Students' Reproductive Health Understanding Level Scale (α=0.328) and interviews. Data were analyzed using descriptive percentage formula and Wilcoxon signed rank test. The results showed that the level of understanding of students about adolescent reproductive health is in the low criteria with an average value of 55.75%. Based on the results of the Wilcoxon signed rank test, it shows that there is an effect of providing information helps on the level of understanding of adolescent reproductive health. With the provision of information helps, students can gain an understanding of the material presented, namely the understanding of women's reproductive health. In addition, there is a prevention function so that students are able to avoid irresponsible behavior towards their own reproductive health.